A 3D micromechanics-based failure criterion for fiber reinforced composites under longitudinal compression. (October 2022) - Wang, Xiaodong; Guan, Zhidong; Liu, Na; Zhang, Mi; Li, Zengshan; Meng, Qingchun; Du, Shanyi
Highlights: Propose a novel 3D longitudinal compressive failure criterion for composites. Cross-scale stress formula are derived to determine failure at micro scale. Two dominated failure modes are analyzed and considered in failure criterion. Key parameters of the longitudinal compressive strength are analyzed. Abstract: A novel micromechanics-based failure criterion for longitudinal compressive failure of fiber reinforced composites is proposed based on the cross-scale stress calculation formula. Two failure modes, fiber bending failure and inter-fiber shear failure, are considered in the failure criterion, judged by the micro-scale stress inner fiber and inter fiber, respectively. The validity of the failure criterion on predicting strength and failure mode is proved by micro-scale finite element models and the existing experimental results. Final, the key effect parameters of longitudinal compressive strength are discussed. The proposed failure criterion can be used for composite structures simulation and composite materials performance design.